Adipic acid directed self-healable supramolecular metallogels of Co(ii) and Ni(ii): intriguing scaffolds for comparative optical-phenomenon in terms of third-order optical non-linearity. Issue 35 (22nd August 2022) - Lepcha, Gerald; Singha, Tara; Majumdar, Santanu; Pradhan, Amit Kumar; Das, Krishna Sundar; Datta, Prasanta Kumar; Dey, Biswajit
Abstract : Adipic acid-directed supramolecular self-healing Co(ii ) and Ni(ii )-metallogels have been achieved to explore a comparative study of third order optical non-linearity. Abstract : Two brilliant outcomes of supramolecular self-assembly directed, low molecular weight organic gelator based self-healable Co(ii ) and Ni(ii ) metallogels were achieved. Adipic acid as the low molecular weight organic gelator and dimethylformamide (DMF) solvent are employed for the metallogelation process. Rheological analyses of both gel-scaffolds reveal mechanical toughness as well as visco-elasticity. Thixotropic behaviours of both the gels were scrutinized. Morphological variations due to the presence of two different metal ions with diverse metal–ligand coordinating interactions were established. The mechanistic pathways for forming stable metallogels of Co(ii )-adipic acid (Co-AA) and Ni(ii )-adipic acid (Ni-AA) were judiciously developed through infrared absorption spectral analysis. The nonlinear optical properties, such as the third-order process, of these synthesized metallogels were scrutinized by means of the Z -scan method at a beam excitation wavelength of 750 nm by a femtosecond laser with different excitation intensities ranging from 64 to 140 GW cm −2 . The third-order nonlinear optical susceptibility ( χ (3) ) of the order of 10 −14 esu was obtained from the measured Z -scan data. Both the metallogels exhibit positive nonlinear refraction and reverse saturable (RSA) absorption at high-intensity excitation. Co(ii ) and Ni(ii ) metallogels show nonlinear refractive indices ( n 2 I ) of (3.619 ± 0.146) × 10 −6 cm 2 GW −1 and (3.472 ± 0.102) × 10 −6 cm 2 GW −1, respectively, and two photon absorption coefficients ( β ) of (1.503 ± 0.045) × 10 −1 cm GW −1 and (1.381 ± 0.029) × 10 −1 cm GW −1 at an excitation intensity of 140 GW cm −2 . We also studied the optical limiting properties with a limiting threshold of 9.57 mJ cm −2 . Therefore, both metallogels can be considered promising materials for photonic devices: for instance, for optical switching and optical limiting.